A review of the development and application of space miniature mass spectrometers. (September 2018) - Ren, Zhengyi; Guo, Meiru; Cheng, Yongjun; Wang, Yongjun; Sun, Wenjun; Zhang, Huzhong; Dong, Meng; Li, Gang
Abstract: This article reviews the recent development and application of four types of space miniature mass spectrometers including magnetic sector mass spectrometer, quadrupole mass spectrometer, ion trap mass spectrometer and time-of-flight mass spectrometer. The advantages and the disadvantages of such mass spectrometers are briefly discussed. Finally, the expectations for improved properties and development trends of these mass spectrometers are presented. Highlights: In the last few decades, the application of miniature mass spectrometer in space field is reviewed. The further development prospect of miniature mass spectrometer in space is provided. The advantages and the disadvantages of four types of space miniature mass spectrometers are briefly discussed.